Characteristics of lacustrine dolomitic rock reservoir and accumulation of tight oil in the Permian Fengcheng Formation, the western slope of the Mahu Sag, Junggar Basin, NW China. (July 2019) - Zhang, Guoyin; Wang, Zhizhang; Guo, Xuguang; Sun, Yanan; Sun, Le; Pan, Lu
Highlights: Extensive dolomitic rocks are the favorable lithologies for tight oil. Microscale dissolution pores and fractures are the major reservoir spaces. We summarize two different types of tight oil accumulation plays. Abstract: The Permian Fengcheng Formation in the western slope of the Mahu Sag, which is located in the Junggar Basin, NW China, has long been considered to be a high-quality source rock in this area. The lacustrine dolomitic rocks within the Fengcheng Formation has recently been reported to have a good tight oil potential as a special type of tight oil reservoir. However, the characteristics of the tight reservoir and tight oil accumulation, which are key factors for commercial development, are not well documented. We conducted a comprehensive reservoir characterization using petrological (core, thin section, scanning electron microscope, and nanoscale computed tomography) and geophysical (seismic and well logging) data. The Fengcheng Formation contains extensive dolomitic rocks deposited around the evaporite under a saline lacustrine environment accompanied by volcanic activities. The western slope of the Mahu Sag can be divided into two zones: the Wufeng Fault Zone and Fengnan Slope Zone. Dolomitic rock reservoirs and tight oil accumulation exist in both zones. Salt minerals, feldspar, calcite, and dolomite in the dolomitic rocks are susceptible to dissolution, and secondary intergranular or intragranular dissolution pores are the major reservoir spaces. Abundant nanoscale pores exist in the dolomitic rocks, but microscale pores, which dominate in volume, play a more important role. Brittle dolomitic rocks commonly develop fractures, but the Wufeng Fault Zone develops far more fault-related fractures than the Fengnan Slope Zone. The oil properties of the Wufeng Fault Zone and the Fengnan Slope Zone are also different. We propose that these two zones are two different types of tight oil accumulation plays: a fracture controlled accumulation play and a pore controlled accumulation play.